The Changing Society And The Role of Indonesia Defense University As Country Defense Axis - Mundayat, Aris Arif (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2018)
This study discusses the concept of defending the country in by considering the context of the development of Indonesian society in the global era and democracy. The diversity of consciousness that arise therefore, are challenge for Indonesia. This qualitative research-based study found that the various phenomena mentioned above are essentially challenge to the interests of the state because they de territorialize the logic of state territorialism, through the form of postnationalist logical thinking. This study is an attempt to define the role of the Indonesian Defense University to form the Axis of State Defense as a strategic network to respond the dynamic of socio-political consciousness constructively. This study contributes a number of important academic concepts to be discussed and further developed.Keywords: Defense the country;Â  Ideology; Globalization, Faithology; Post-nationalistÂ